2021
DOI: 10.1002/ange.202013687
|View full text |Cite
|
Sign up to set email alerts
|

Efficient Amination of Activated and Non‐Activated C(sp3)−H Bonds with a Simple Iron–Phenanthroline Catalyst

Abstract: A readily available catalyst consisting of iron dichloride in combination with 1,10‐phenanthroline catalyzes the ring‐closing C−H amination of N‐benzoyloxyurea to form imidazolidin‐2‐ones in high yields. The C−H amination reaction is very general and applicable to benzylic, allylic, propargylic, and completely non‐activated aliphatic C(sp3)−H bonds, and it also works for C(sp2)−H bonds. The surprisingly simple method can be performed under open flask conditions.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 69 publications
(18 reference statements)
0
5
0
Order By: Relevance
“…[41][42][43][44][45][46][47][48][49][50][51][52][53] Recently, we discovered dioxazolones can undergo intermolecular N-N coupling with arylamines to make hydrazides under either iridium or iron catalysis. [54][55][56][57][58][59][60][61][62][63][64] Mechanistic studies of the Ir-catalyzed system indicated an outer-sphere nucleophilic attack of the nitrogen group of Ir-nitrenoid intermediate by amine leads to the N-N coupling product.…”
Section: Resultsmentioning
confidence: 99%
“…[41][42][43][44][45][46][47][48][49][50][51][52][53] Recently, we discovered dioxazolones can undergo intermolecular N-N coupling with arylamines to make hydrazides under either iridium or iron catalysis. [54][55][56][57][58][59][60][61][62][63][64] Mechanistic studies of the Ir-catalyzed system indicated an outer-sphere nucleophilic attack of the nitrogen group of Ir-nitrenoid intermediate by amine leads to the N-N coupling product.…”
Section: Resultsmentioning
confidence: 99%
“…2‐Imidazolidones 17 , which are the key scaffolding in bioactive chemicals, have been synthesized using N‐benzoyloxyureas 16 and ferrous chloride as a catalyst [45]. The C–H amination of propargylic and allylic C(sp 3 )–H bonds were effectively converted into 2‐imidazolidones respectively.…”
Section: Intramolecular Cyclization Methods For N‐heterocycle Synthesismentioning
confidence: 99%
“…catalyst [45]. The C-H amination of propargylic and allylic C(sp 3 )-H bonds were effectively converted into 2-imidazolidones respectively.…”
Section: °Cmentioning
confidence: 99%
“…In 2021, Eric and coworkers reported a robust protocol for the synthesis of cyclic amides 188 from direct C(sp 3 )−H amidation of benzylic, allylic, propargylic, and completely non‐activated aliphatic C(sp 3 )−H bonds 187 using a simple iron salt in combination with a readily available ligand under mild conditions (Scheme 48). [68] They commenced the optimization study by selecting N‐benzoyloxyurea as a model substrate. This revealed that 10 mol % FeCl 2 .4H 2 O as a catalyst, 3.0 equiv.…”
Section: Iron Catalyzed C(sp3)−h Functionalization Reactionsmentioning
confidence: 99%